DETRITAL ZIRCON COMPOSITION OF U-Pb AGES AND HF ISOTOPE OF THE HUNSHANDAKE SANDLAND AND IMPLICATIONS FOR ITS PROVENANCE - Xie J.; Wu F.Y.; Ding Z.L. (My University, 2007)
Detrital zircon compositions of in-situ U-Pb ages and Hf isotope were measured for sand samples since the Last Glacial Maxim (LGM) from the Hunshandake sandland, and compared with surrounding potential source areas. We found that U-Pb age spectra of samples from the Hunshandake sandland can be mainly divided into three groups (2.6-2.3Ga, 2.2-1.6Ga and Phanerozoic age 100-500Ma). The older two groups and some Phanerozoic zircons with negative εHf(T) values maybe were derived from the Yanshan Fold Belt in the northern part of the North China Craton, and other Phanerozoic zircons with positive εHf(T) values may originated from the eastern part of the Central Asian Orogenic Belt. The present sands have the similar composition characteristics of zircon U-Pb age spectra and ε Hf(T) values with the LGM sands. Meanwhile, comparing with the sand samples from central-southern Mongolia and central Tarim, we found that the sand samples of central-southern Mongolia mainly come from Phanerozoic high mountains of the Central Asian Orogenic Belt, however, much difference of zircon U-Pb ages and Hf isotopes occurs between the samples of the Hunshandake and Taklimakan deserts, indicating that the material of the western large desert contributes little to the eastern sandland.
Keywords: HF ISOTOPE; HUNSHANDAKE SANDLAND; PROVENANCE; U-Pb AGES; ZIRCON